Secular stagnation and the demographic transition: a factor model approach - Cordeiro, João Maria Pereira (2021)
Secular stagnation is a tale of ageing economies permanently constrained in a below full-employment steady-state due to aggregate demand shortfalls. Using a factor model combined with a VAR for seven key macro-series augmented with demographics, we investigate the link between the demographic transition and macroeconomic trends. We find that, while a single variable offers an insufficient representation of the recent population dynamics, two factors can account for almost the entire variance of the five variables that best describe the demographic transition. Our results indicate that demographics have exerted significant deflationary and contractionary pressures in the Euro Area and Japan since 1970.